2022
DOI: 10.5387/fms.2021-19
|View full text |Cite
|
Sign up to set email alerts
|

Psychologic distress and QOL in medical staff after a disaster: A longitudinal 4-year study

Abstract: Aiming to improve postdisaster care of medical staff, we conducted an early and ongoing assessment of postdisaster psychologic distress and quality of life (QOL) in one center of a disasterresponse hospital. Twelve days after the Great East Japan Earthquake, as the Fukushima Daiichi Nuclear Power Plant crisis was unfolding, we began a survey to examine the physical and mental state of medical staff to assess their motivation toward work. Surveys were administered in March 2011

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…In the prepandemic period, the MC scores were higher than in this study (Sabbah et al, 2013), which can highlight its impact on medical students' mental health. Several studies also reported this finding showing the psychological distress among students in addition to their deteriorated emotional states (Passos et al, 2022;Taylor et al, 2022;Yabuki et al, 2022). The long-term consequences of this decline may affect medical students' academic and professional performance and call for the need to support this sensitive group psychologically.…”
Section: Discussionmentioning
confidence: 85%
“…In the prepandemic period, the MC scores were higher than in this study (Sabbah et al, 2013), which can highlight its impact on medical students' mental health. Several studies also reported this finding showing the psychological distress among students in addition to their deteriorated emotional states (Passos et al, 2022;Taylor et al, 2022;Yabuki et al, 2022). The long-term consequences of this decline may affect medical students' academic and professional performance and call for the need to support this sensitive group psychologically.…”
Section: Discussionmentioning
confidence: 85%